(untitled) (Global Journal of Human-Social Science, 2022)
Changing geopolitical realities in recent years reveals significant challenges and shortcomings in the global system that had led the world to its present parlous state and has accentuated national social and societal concerns An important issue that requires a response from national Governments in many countries as well as more social research is the protection of workers claims in case of insolvency This issue has multiple aspects such as legislative Regulation of bankruptcy insolvency and restructuring creation of guarantee institutions that should be designed to protect employees claims Information support of former employees and fosters their mobility territorial coordination and internationalization shares of labor market information recognition of formal informal and non-formal education and training social dialogue etc In this article we concentrate on the methodology of a new Business Enabling Environment rating projected by the World Bank Group and analyze the methodology of it trying to determine if the above-mentioned issue as well as the protection of workers rights and human social interests of society at large have been reflected in the concept of the project